Marketing Communication Online Strategy Of CV. Multicraft Indonesia - Kharis Marpurdianto; Arya Putra Dwi Kusuma (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2022)
This study aims to analyze the marketing communication strategy used by CV. Multicraft Indonesia to increase its products of the company. This study utilized the qualitative descriptive analysis approach. The data was collected primarily by interview the Head Staff Marketing of CV. Multicraft Indonesia as the one who took responsibility to give policy abd planning, especially in marketing products. In addition, the study utilized secondary data collected during the research on the communication strategies implemented in the company. The results saw that CV. Multicraft Indonesia used four methods in marketing communication online strategy. They are (1) an advertisement on a marketplace platform such as shopee, Tokopedia, Lazada, (2) sales promotion that consists of five sub-bab (voucher, flash sale, promo store, free shipping cots, and point of sale & merchandising, (3) a “reseller” method for those who want to be a reseller or partner of CV. Multicraft indonesia, and (4) endorsement by choosing public figures or celebrities who have a big impact on the products or brand.